Characterization of a membrane-associated estrogen receptor in breast cancer cells and its contribution to hormone therapy resistance using a novel selective ligand. Issue 201 (July 2020) - Niwa, Toshifumi; Takanobu, Junko; Suzuki, Kanae; Sato, Yuta; Yamaguchi, Yuri; Hayashi, Shin-ichi
Highlights: Novel specific ligand to membrane-associated estrogen receptor (mER) was prepared. The mER specific ligand contributes to cell proliferation from outside of the cells. The mER mediates both PI3K/akt and MAPK (Erk1/2) pathways. The mER probably consists of sub-localized forms of nuclear ERα. The mER signaling pathway may help generate hormone therapy resistance. Abstract: The estrogen receptor (ER) plays a role in the progression of hormone-dependent breast cancer and is a hormone therapy target. Estrogen acts as a transcription factor (genomic action) and also produces a quick non-genomic reaction through intracellular signaling pathways. The membrane associated ER (mER) may regulate both these signals and hormone therapy resistance. However, the details remain unclear because a reliable method to distinguish the signals induced by the estradiol (E2)-mER and E2-nuclear ER complex has not been established. In the present study, we prepared the novel ligand Qdot-6-E2, selective for mER, by coupling E2 with insoluble quantum dot nano-beads. We investigated the characteristics of mER signaling pathways and its contribution to hormone therapy resistance using different cell lines including estrogen depletion resistant (EDR) cells with different mechanisms. Qdot-6-E2 stimulated proliferation of nuclear ER-positive cells, but nuclear ER-negative cells showed no response. In addition, Qdot-6-E2 indirectly activated nuclear ER and increased mRNA expression of target genes. We confirmed that E2 was not dissociated from Qdot-6-E2 using a mammalian one-hybrid assay. We visually demonstrated that Qdot-6-E2 acts from the outside of cells. The gene expression profile induced by Qdot-6-E2-mER was different from that induced by E2-nuclear ER. The effect of anti-ER antibody, the GFP-ER fusion protein localization, and the effect of palmitoyl acyltransferase inhibitor also indicated the existence of mER. Regarding intracellular phosphorylation signaling pathways, the MAPK (Erk 1/2) and the PI3K/Akt pathways were both activated by Qdot-6-E2. In EDR cells, only nuclear ER-positive cells showed increased cell proliferation with increased localization of ERα to the membrane fraction. These findings suggested that Qdot-6-E2 reacts with ERα surrounding the cell membrane and that mER signals help the cells to survive under estrogen-depleted conditions by re-localizing the ER to use trace amounts of E2 more effectively. We expect that Qdot-6-E2 is a useful tool for studying the mER.